1993
DOI: 10.1088/0022-3727/26/10/035
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the 'cold' electron emission characteristics of diamond coated molybdenum electrodes and polished bulk graphite surfaces

Abstract: Details are given of an experimental study of field emission characteristics of diamond-coated Mo electrodes: in particular, a transparent anode imaging technique was used to monitor the spatial distribution of the individual emission centres. This study has revealed the important fact that substantial emission can be obtained at fields as low as 5 MV m-1. In order to investigate the physical nature of the emission process, a comparative study has been made of emission obtained from a diamond-coated electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(72 citation statements)
references
References 9 publications
1
71
0
Order By: Relevance
“…[1][2][3][4] Initial interest was stimulated by the prospect of electron emission at very low electric fields due to the low electron affinity of the carbon in the diamond form when terminated with hydrogen: the diamond surface, in fact, has a negative electron affinity ͑NEA͒. Various carbon based cold cathodes including diamond, 5 nanodiamond, 6 diamondlike carbon ͑DLC͒ and tetrahedral amorphous carbon, 7,8 carbon nanotubes, 9,10 and nanoclustered carbon [11][12][13][14] have all been shown to emit electrons at reasonably low electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Initial interest was stimulated by the prospect of electron emission at very low electric fields due to the low electron affinity of the carbon in the diamond form when terminated with hydrogen: the diamond surface, in fact, has a negative electron affinity ͑NEA͒. Various carbon based cold cathodes including diamond, 5 nanodiamond, 6 diamondlike carbon ͑DLC͒ and tetrahedral amorphous carbon, 7,8 carbon nanotubes, 9,10 and nanoclustered carbon [11][12][13][14] have all been shown to emit electrons at reasonably low electric fields.…”
Section: Introductionmentioning
confidence: 99%
“…The experimentally observed current-voltage relation fits the Fowler-Nordheim expression (Eq. 4) corresponding to tunneling through a barrier [20).…”
Section: Cold Cathode Electron Emissionmentioning
confidence: 99%
“…The effective work function and emission area can be determined from the slope and intercept, respectively, of a plot of ln(J/E2) vs l/E, assuming a known value of~. The value of the effective work function tends to be quite low [26], typically less than 0.1 eV, and the emission comes from isolated, discrete sites [20] which are often very low in density. It has been demonstrated via ultra-violet photoelectron spectroscopy [20,27] that under certain circumstances, diamond is a negative electron affinity (NEA) material (i. e., the bottom of the conduction band lies above the vacuum level) with a 5.5 eV band gap.…”
Section: Cold Cathode Electron Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of research groups have shown experimental results in which the electron emission from polycrystalline diamond and diamond like carbon ͑DLC͒ ͑or amorphous carbon͒ has been achieved at low threshold fields. [2][3][4][5][6][7] In this article we will develop a model that can be used to explain the observed electron emission characteristics of polycrystalline diamond using a model which involves the presence of DLC ͑or amorphous carbon͒ at/in the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%